Is preoperative neutrophil-lymphocyte ratio important in patients who undergo radical nephroureterectomy for upper urinary tract urothelial cancer? (Annals of Medical Research, 2022)
Aim: To evaluate the effect of preoperative blood count parameters and pathological features on recurrence in patients who underwent Radical Nephroureterectomy (RNU) and Bladder Cuff Resection for Upper Urinary Tract Urothelial Cancer (UTUC).Material and Methods: The data of patients who underwent RNU for UTUC were reviewed retrospectively. According to the follow-up data, the patients were divided into 2 groups as recurrence and non-recurrence. It was examined whether there was a difference between the groups in terms of preoperative blood count parameters (neutrophil, lymphocyte, eosinophil, monocytes, neutrophil-lymphocyte ratio, and platelet-lymphocyte ratio) and final pathological features. A p
Keywords: Urothelial cancer; upper urinary tract; radical nephroureterectomy; recurrence; neutrophil-lymphocyte ratio